Common, But Neglected: A Comprehensive Review of Leg Ulcers in Sickle Cell Disease. (August 2021) - Sahu, Tarun; Verma, Henu Kumar; Ganguly, Satyaki; Sinha, Meenakshi; Sinha, Ramanjan
ABSTRACT: OBJECTIVE: To compile available evidence to better understand the management of leg ulcers in sickle cell disease (SCD), as well as describe potential therapeutic steps that may be required to improve the quality of life of patients with SCD leg ulcers. DATA SOURCES: MEDLINE, PubMed, EMBASE, and Web of Science databases STUDY SELECTION: A comprehensive search was conducted to retrieve relevant studies using the keywords "sickle cell disease and leg ulcer, " "ulcer treatments, diagnosis and sickle cell, " and "wound sickle cell." Studies published through July 2020 were included. DATA EXTRACTION: Two independent authors selected all studies that assessed the relationship between leg ulcer and SCD identified from online databases. DATA SYNTHESIS: The authors have summarized updated information on pathophysiology (vasculopathy linked to chronic hemolysis and endothelial dysfunction), diagnosis, and available treatment options to unravel the dermohematologic connection between leg ulcers and SCD. CONCLUSIONS: It is the authors' hope that this detailed discussion of the information available on leg ulcers and SCD will lead to a better appreciation of this clinical problem by the clinicians and researchers and in turn have a long-term positive effect on the quality of life of patients with SCD. Researchers should design new trials considering these insights and potential therapeutic approaches based on current knowledge.